2013
DOI: 10.1093/mp/sst082
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cytokinesis by Exocyst Subunit SEC6 and KEULE in Arabidopsis thaliana

Abstract: Proper vesicle tethering and membrane fusion at the cell plate are essential for cytokinesis. Both the vesicle tethering complex exocyst and membrane fusion regulator KEULE were shown to function in cell plate formation, but the exact mechanisms still remain to be explored. In this study, using yeast two-hybrid (Y-2-H) assay, we found that SEC6 interacted with KEULE, and that a small portion of C-terminal region of KEULE was required for the interaction. The direct SEC6-KEULE interaction was supported by furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
70
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 64 publications
(104 reference statements)
3
70
3
Order By: Relevance
“…Localization studies of specific Arabidopsis exocyst subunits also supported conserved roles in polarized exocytosis and cytokinesis in plants. Localization studies have shown EXO70, SEC6, and SEC8 at the growing tip of pollen tubes (Hála et al, 2008), EXO70A1 at the stigmatic papillar plasma membrane (Samuel et al, 2009), SEC3a, SEC6, SEC8, SEC15b, EXO70A1, and EXO84b at the root epidermal cell plasma membrane and developing cell plate (Fendrych et al, 2010Wu et al, 2013;Zhang et al, 2013;Rybak et al, 2014), and SEC3a at the plasma membrane in the embryo and root hair (Zhang et al, 2013). Similar to the yeast exocyst mutants, vesicle accumulation has also been observed in the exo70A1 and exo84b mutants (Fendrych et al, 2010;Safavian and Goring, 2013).…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…Localization studies of specific Arabidopsis exocyst subunits also supported conserved roles in polarized exocytosis and cytokinesis in plants. Localization studies have shown EXO70, SEC6, and SEC8 at the growing tip of pollen tubes (Hála et al, 2008), EXO70A1 at the stigmatic papillar plasma membrane (Samuel et al, 2009), SEC3a, SEC6, SEC8, SEC15b, EXO70A1, and EXO84b at the root epidermal cell plasma membrane and developing cell plate (Fendrych et al, 2010Wu et al, 2013;Zhang et al, 2013;Rybak et al, 2014), and SEC3a at the plasma membrane in the embryo and root hair (Zhang et al, 2013). Similar to the yeast exocyst mutants, vesicle accumulation has also been observed in the exo70A1 and exo84b mutants (Fendrych et al, 2010;Safavian and Goring, 2013).…”
mentioning
confidence: 82%
“…A number of Arabidopsis exocyst subunit loss-offunction mutants display severe growth defects; thus, flowering is compromised in these mutants (Fendrych et al, 2010;Wu et al, 2013;Zhang et al, 2013). As we were interested in investigating if the exocyst subunits are required in the stigmatic papilla to accept compatible pollen, a focused strategy was adopted to knockdown the expression of individual exocyst subunit genes.…”
Section: Strategies For the Rna Silencing Of Exocyst Subunit Genes Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in Arabidopsis (Arabidopsis thaliana) and maize (Zea mays) have implicated the exocyst in the regulation of pollen tube and root hair growth, seed coat deposition, response to pathogens, cytokinesis, and meristem and stigma function (Cole et al, 2005;Synek et al, 2006;Hála et al, 2008;Fendrych et al, 2010;Kulich et al, 2010;Pecenková et al, 2011;Safavian and Goring, 2013;Wu et al, 2013;Safavian et al, 2015;Zhang et al, 2016). The growth arrest of pollen tubes in sec8, sec6, sec15a, and sec5a/sec5b single and double mutants (Cole et al, 2005;Hála et al, 2008) or following treatment with the EXO70 inhibitor ENDOSIDIN2 (Zhang et al, 2016), and of root hairs in maize root hairless1 (rth1) SEC3 mutant (Wen et al, 2005), the inhibition of seed coat deposition in the sec8 and exo70A1 mutants (Kulich et al, 2010), and stigmatic papillae function in exo70A1 mutant plants (Safavian and Goring, 2013;Safavian et al, 2015) have implicated the exocyst in polarized exocytosis in plants.…”
mentioning
confidence: 99%